2021
DOI: 10.1186/s13018-021-02679-w
|View full text |Cite
|
Sign up to set email alerts
|

External fixation versus elastic stable intramedullary nailing in the treatment of open tibial shaft fractures in children

Abstract: Introduction External fixator (EF) is a popular choice for open tibial fractures, but pin tract infection (PTI) and refracture are common complications. Elastic stable intramedullary nail (ESIN) has been reported in the treatment for open tibial fractures. This study aims to compare the clinical outcomes of EF vs. ESIN in the treatment for open tibial shaft fracture in children retrospectively. Methods Patients aged 5–11 years with Gustilo-Anderson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…As for the patient's weight, we documented a weight range of 16 to 32 kg, with an average patient weight of 25.3 kg. This outcome is similar to a study (Hong et al, 2021), which documented a mean weight of 28.4 kg.…”
Section: Discussionsupporting
confidence: 90%
“…As for the patient's weight, we documented a weight range of 16 to 32 kg, with an average patient weight of 25.3 kg. This outcome is similar to a study (Hong et al, 2021), which documented a mean weight of 28.4 kg.…”
Section: Discussionsupporting
confidence: 90%
“…However, several studies in pediatric patients have shown that definitive stabilization within 3 days of injury has improved outcomes and reduces hospital stays [ 7 , 8 ]. External fixation has a documented role in open tibial fractures [ 9 ], whereas elastic intramedullary nailing can be used in selected Grade II and IIIA open tibial fractures with limited contamination [ 10 ]. Our patient had a Gustilo-Anderson grade IIIB multi-fragmentary fracture of the left tibia-fibula with multiple extensive CLW from groin to toe and a closed transverse fracture of the right tibia with a clean lacerated wound over distal shin not communicating with the fracture and a CLW over the right groin.…”
Section: Discussionmentioning
confidence: 99%
“…The radiological union was faster in the ESIN group than in the EF group, and pin tract infection was the most troublesome complication in the EF group. Based on their study, ESIN is a viable option in selected patients of GA grades II and IIIA open tibial fractures with clinical outcomes comparable to those of external fixation [33]. Ramseirer et al reported the treatment results of thirty-five patients affected by open femur fractures; EF was used in 23 cases, while 12 had an IM device (6 rigid nails and 6 elastic flexible nails).…”
Section: Discussionmentioning
confidence: 99%
“…External fixation in pediatric patients has shown more complications than in adult patients, such as pin tract infection and a longer healing time; whenever possible, the use of IM devices for the treatment of open femur fractures in children should be considered, especially for grade I open injuries. If EFs are used, avoiding malunion may decrease the refracture rate, and the primary application of, or secondary change to, an IM device can be considered [33,34]. Time to surgery did not vary by fracture grade, although there was a trend toward more rapid surgical interventions in the grade 2 and grade 3 injuries than in the grade 1 fractures; in the literature, it was reported that, despite a delay in surgery of 6 h, there was no difference in the overall rate of infection [35,36].…”
Section: Choice Of Treatment: When and Whichmentioning
confidence: 99%